Layered composite electric contact material and preparation method thereof
In the preparation process of layered composite electrical contact materials, continuous thermal composite and high-temperature heat treatment methods are used to form a metallurgical layer, which solves the problems of material edge cracking, thermal interface layering and low material yield, and achieves high quality and reliability production of electrical contact materials.
Patent Information
- Application Number
- CN202411643656.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
During the preparation process, existing layered composite electrical contact materials have problems such as material edge cracking, thermal interface layering and low material yield, which is difficult to meet the reliability and service life requirements of low-voltage electrical products.
Using continuous thermal composite and high-temperature heat treatment methods, metallurgical bonds are first formed between the silver-based working layer, the sterling silver layer and the brazing layer, and then cold composite and high-temperature heat treatment are carried out with copper-based and iron-based materials to form a metallurgical layer and improve the material bond strength and temperature resistance.
It effectively avoids the problem of interface layering of materials in hot working conditions, improves the quality stability and material yield of electrical contacts, and simplifies the production process and reduces costs.
Smart Images

Figure CN119480475A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electric contact materials, and in particular to a layered composite electric contact material and a preparation method thereof. Background Art
[0002] Layered composite electrical contact materials have attracted wide attention in the low-voltage electrical appliance industry due to their low use of precious metals, low cost, and good comprehensive performance. In particular, contacts used in conjunction with bimetallic strips must use layered composite contacts with Ni-based or Fe-based materials on the welding surface to meet the welding strength requirements. Domestic methods for preparing layered metal-based composite materials include cold pressing composite, explosive composite, welding, and other methods. Among them, cold composite is one of the main methods for mass production of layered metal-based composite materials at home and abroad. Cold composite requires that the composite deformation must be greater than 50%, otherwise stratification will occur. Since multiple materials with different performances are involved, their physical properties vary greatly. Increasing the deformation will cause one of the layers to crack, which seriously affects the quality of layered composite electrical contact products. For example, AgSnO2 / Ag / Cu / Fe layered composite electrical contacts, due to the poor plasticity of AgSnO2, a large composite deformation will cause AgSnO2 to crack. The hot composite process has high requirements for equipment, the process is relatively complex, and the surface of the material is prone to oxidation, resulting in interface stratification. The efficiency of explosive composite is extremely low, the damage to the environment is serious, the safety factor is low, and it has not been widely used in production. In addition, when cold composite and hot composite layered electrical contact materials are used in combination with bimetallic strips, especially when they are in high-power service, the contacts are seriously heated and the temperature is high, which leads to a significant deterioration of the composite interface bonding force in the hot state, which easily leads to hot stratification.
[0003] Therefore, there is an urgent need for a preparation method of a layered composite electrical contact material to make up for the defects of the existing processing technology and realize high-quality mass production of layered composite electrical contact materials, thereby improving the reliability and service life of low-voltage electrical products.
[0004] After searching, it was found that patent CN101034632A uses diffusion welding → rolling to connect the silver alloy working layer, silver alloy solder layer and copper substrate layer. The method described in this invention requires that the layered materials are placed in a vacuum or atmosphere furnace at the same time and in full. The material size is limited by the furnace cavity, which is not conducive to mass production and efficient production, and ultimately leads to the problem of low yield rate. In addition, the diffusion welding process is generally used for two-layer welding. For diffusion welding of materials with more than three layers, it is difficult to control the welding quality of each layer.
[0005] Patent CN107591257A adopts cold compounding → continuous annealing → rolling → striping → blanking to connect the silver alloy working layer, silver alloy or pure silver layer, copper intermediate layer and iron welding layer and solder layer to prepare a silver-based layered composite electrical contact material. Although the patent can continuously batch composite layered materials, the method described in the patent requires an increase in deformation during the cold compounding process when heat-treated after cold compounding. It is not suitable for silver metal oxide AgMeO with poor plasticity or low silver content, which will cause cracks in the working layer. In addition, the temperature resistance of the cold-compounded silver-copper composite interface is poor, and stratification will occur above 600°C, which cannot meet the requirements of use under hot working conditions. And the solder layer in the patent has a composite structure at the welding interface, which is mainly used to improve the contact welding performance of the next process.
[0006] Therefore, it is necessary to develop a preparation method for layered composite electrical contact materials, which can not only avoid the cracking of silver-based oxide AgMeO with poor plasticity and interface stratification under hot working conditions, but also realize continuous batch production, thereby effectively ensuring the reliability and service life of low-voltage electrical products. Summary of the invention
[0007] In view of the defects in the prior art, an object of the present invention is to provide a layered composite electrical contact material and a preparation method thereof.
[0008] According to one aspect of the present invention, there is provided a method for preparing a layered composite electrical contact material, comprising:
[0009] The silver-based working layer, the pure silver layer and the solder layer are continuously thermally compounded, and then continuously heat treated to fuse the solder layer and the pure silver layer to obtain a three-layer composite material;
[0010] Compounding the copper-based material and the iron-based material in two layers and heat treating them to obtain a two-layer copper-iron-based composite material;
[0011] Cold-compounding the three-layer composite material and the two-layer copper-iron-based composite material to obtain a silver-based layered composite electrical contact material;
[0012] The silver-based layered composite electrical contact material is subjected to high-temperature heat treatment so that the solder layer and the copper-based material are fused to obtain a material strip;
[0013] Rolling the strip to a desired thickness;
[0014] The rolled material strip is directly blanked or cut into strips and then rolled to obtain a layered composite electrical contact material of required specifications.
[0015] Optionally, the silver-based working layer, the pure silver layer and the solder layer are continuously thermally composited and then continuously heat treated, wherein:
[0016] The thickness of the solder layer is 0.05 to 0.4 mm;
[0017] The thermal compound atmosphere is argon or nitrogen atmosphere, and the flow rate is 0.2~5m -3 / h; the thermal composite temperature is 580~900℃; the material pulling speed is 0.1~10m / min, and the composite deformation is 60%~90%;
[0018] The continuous heat treatment temperature is 550°C to 800°C, and the speed is 0.5 to 10 m / min.
[0019] Optionally, the copper-based material and the iron-based material are subjected to two-layer composite and heat treatment, wherein: cold composite or hot composite is adopted, the composite deformation is 50% to 90%, the heat treatment temperature is 600°C to 900°C, and the heat treatment atmosphere is any one of hydrogen, nitrogen and nitrogen-hydrogen mixed gas.
[0020] Optionally, the three-layer composite material and the two-layer copper-iron-based composite material are cold-compounded, wherein: the cold-compounding deformation is 20% to 60%, the thickness of the solder fusion layer after compounding is within 0.1 mm, and the cold-compounding speed is 0.1 to 10 m / min.
[0021] Optionally, the silver-based composite electrical contact material is subjected to a high-temperature heat treatment, wherein: the protective atmosphere is any one of argon, nitrogen, and a mixture of argon and nitrogen, and the gas flow rate is 0.2 to 5 m -3 / h; the temperature is 500-750°C, and the material pulling speed is 0.2-5m / min.
[0022] Optionally, the material strip is rolled to a desired thickness, wherein the rolling deformation does not exceed 20% and the rolling speed is 0.5-20 m / min.
[0023] Optionally, the rolled strip is directly blanked or stripped and then rolled, wherein:
[0024] The direct blanking includes: directly punching the rolled material strip into the required layered composite contacts;
[0025] The stripping followed by rolling comprises: dividing the rolled material strip into a plurality of narrow material strips, and then rolling them to obtain a layered composite joint strip with patterns on the welding surface.
[0026] According to another aspect of the present invention, there is provided a layered composite electrical contact material, which is prepared using the above-mentioned method for preparing a layered composite electrical contact material, wherein the layered composite electrical contact material sequentially comprises a silver-based working layer, a pure silver layer, a solder layer, a copper-based intermediate layer and an iron-based welding layer, each material layer being a plate or a strip, and the solder layer forms a metallurgical bond with the pure silver layer and the copper-based intermediate layer, respectively.
[0027] Optionally, the thickness of the silver-based working layer accounts for 5% to 30% of the total thickness of the layered composite electrical contact material, and the sum of the thicknesses of the pure silver layer, solder layer, copper-based intermediate layer, and iron-based welding layer accounts for 30% to 90% of the total thickness of the layered composite electrical contact material.
[0028] Optionally, the material of the silver-based working layer is any one of AgSnO2 series, AgNi series, AgCdO series, AgCuO series, AgZnO series and AgFe series;
[0029] The material of the solder layer is silver alloy solder or copper alloy solder;
[0030] The material of the copper-based intermediate layer is metallic copper or a copper-based alloy;
[0031] The material of the iron-based welding layer is metallic iron or iron-based alloy.
[0032] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0033] 1. The preparation method of the layered composite electrical contact material provided by the present invention is to pre-combine the solder layer with the silver-based material and the pure silver layer, and then perform high-temperature heat treatment to melt the solder layer and fuse it with the pure silver layer; then cold-compound with the copper-based material and the iron-based material, and then perform high-temperature heat treatment to melt the intermediate solder fusion layer, and further fuse it with the copper-based material to form a metallurgical layer, which greatly improves the bonding strength between the silver-based material and the copper-based material, and the interface has good temperature resistance, avoiding the interface stratification problem under hot working conditions, thereby effectively improving the quality stability of the electrical contact and the product yield rate. The method of the present invention is simple, easy to mass produce, and greatly reduces the production cost of the product.
[0034] 2. The layered composite electrical contact material prepared by the present invention meets the requirements for composite interface bonding under cold composite conditions with relatively small deformation, thereby solving the problem that conventional cold composites can only achieve composite interface strength under large composite deformation, and further solving the problem of edge cracking of silver-based oxide materials accompanying conventional large deformation composites, as well as the problem of delamination of layered contacts during service due to poor interface temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0036] Figure 1 The microstructure metallographic image of the interface fusion distribution of Cu and Ag in the AgSnO2(12) / Cu / Fe layered composite material prepared in Example 1 of the present invention;
[0037] Figure 2Schematic diagram of the interface fusion zone between Cu and Ag in the AgSnO2(12) / Cu / Fe layered composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0039] In order to solve the problems of delamination, material cracking and easy delamination at the interface of hot working condition in the prior art, an embodiment of the present invention provides a method for preparing a layered composite electrical contact material, which comprises the following steps:
[0040] S1, continuously thermally compounding the silver-based working layer, the pure silver layer and the solder layer in sequence, and then continuously heat treating the solder layer and the pure silver layer to fuse them to obtain a three-layer composite material;
[0041] S2, compounding and heat treating the copper-based material and the iron-based material in two layers to obtain a two-layer copper-iron-based composite material;
[0042] S3, cold-compounding the three-layer composite material with the two-layer copper-iron-based composite material to obtain a silver-based layered composite electrical contact material;
[0043] S4, subjecting the silver-based layered composite electrical contact material to high-temperature heat treatment, so that the solder layer and the copper-based material are fused to obtain a material strip;
[0044] S5, rolling the strip to a desired thickness;
[0045] S6. The rolled material strip is directly blanked or stripped and then rolled to obtain a layered composite electrical contact material of required specifications.
[0046] In the embodiment of the present invention, a solder layer is added between the two layers of copper-iron-based composite material and the three layers of composite material, respectively. The silver-based material-brazing layer (including a silver-based working layer, a pure silver layer and a solder layer) and the two layers of copper-iron-based composite material (including a copper-based intermediate layer and an iron-based layer) are first cold-compounded, and then subjected to high-temperature heat treatment to melt the solder. The solder fusion layer replaces the existing composite interface layer to firmly connect the silver-based working layer, the pure silver layer and the copper-based intermediate layer. Subsequently, the material is rolled, slit and blanked to finally obtain a layered composite electrical contact material with a well-bonded interface.
[0047] In some embodiments, in step S1, the material of the silver-based working layer is any one of AgSnO2, AgNi, AgCdO, AgCuO, AgZnO and AgFe. The material of the solder layer is a silver alloy solder or a copper alloy solder. The thickness of the solder layer is 0.05 to 0.4 mm; the thermal composite atmosphere is a protective atmosphere such as argon or nitrogen atmosphere to prevent oxidation of the material strip; the flow rate is 0.2 to 5 m -3 / h, if the air flow is too small, it is not enough to isolate the external oxygen, which will cause the material to oxidize; if the air flow is too large, due to the fast airflow, it may cause the surface of the material to take away more heat, making the material temperature lower, thereby affecting the composite bonding strength; the thermal composite temperature is 580~900℃, and the thermal composite temperature is lower than 580℃. Under the same deformation, the interface bite degree is smaller and the bonding strength is lower; if the temperature is too high, the material is softer, and the material is under tension before the composite, which is easy to break; the material pulling speed is 0.1~10m / min, and the material pulling speed is the composite speed. If the material If the material pulling speed is too slow, the production efficiency will be affected. If the material pulling speed is too fast, the uniformity of the composite thickness of the material strip will be poor. The composite deformation is 60% to 90%. If the deformation is small, the bonding strength between the material strip layers will be poor. If the deformation is large, the material strip will crack, especially the edge cracking problem. The continuous heat treatment temperature is 550℃ to 800℃, and the speed is 0.5 to 10m / min. If the temperature is too low or the speed is too fast, the layers will not have time to diffuse and the bonding strength will be poor. If the temperature is too high or the speed is too slow, the solder or brazing material layer will melt and be lost.
[0048] In some embodiments, in step S2, the material of the copper-based intermediate layer is metallic copper or a copper-based alloy; the material of the iron-based welding layer is metallic iron or an iron-based alloy.
[0049] The composite is cold composite or hot composite, and the composite deformation is 50% to 90% to achieve better composite bonding strength; the heat treatment temperature is 600°C to 900°C to achieve metallurgical bonding at the composite interface, that is, the two materials are fused at the composite interface; the heat treatment atmosphere is any one of hydrogen, nitrogen and nitrogen-hydrogen mixed gas, and these non-oxidizing atmospheres can protect the material surface from oxidation at high temperatures.
[0050] In this step, if the composite deformation is too low, the material interface tearing degree is small, and effective micro-region bite cannot be achieved during the composite, which in turn affects the bonding strength. If the deformation exceeds 90%, it will lead to poor deformation and serious distortion of the material. If the heat treatment temperature is too low, it will not melt, and if the temperature is too high (over 900 degrees), the copper alloy will melt slightly as a whole, causing damage to the copper surface.
[0051] In step S3, before cold lamination, cleaning and drying are also included. Specifically, deionized water is used for cleaning and the drying temperature is 40°C to 100°C to ensure the cleanliness and dryness of the interface during the lamination process, which is conducive to achieving a higher composite bonding strength later.
[0052] In some embodiments, in step S3, during the composite process, the solder layer of the three-layer composite material is combined with the copper-based material of the two-layer copper-iron-based composite material, the cold composite deformation is 20% to 60%, the thickness of the solder fusion layer after composite is within 0.1 mm, and the cold composite speed is 0.1 to 10 m / min, thereby achieving a higher composite bonding strength.
[0053] In some embodiments, in step S4, in order to protect the material from being oxidized and to prevent the silver oxide material in the working layer from being reduced, the protective atmosphere is any one of argon, nitrogen, and a mixture of argon and nitrogen, and the gas flow rate is 0.2 to 5 m / s. -3 / h; in order to meet the melting of the solder layer, the temperature point is selected in the solder liquidus-solidus temperature range, the temperature is 500-750°C, and the material pulling speed is 0.2-5m / min, thereby achieving melting and fusion of the solder layer interface, and melting with the silver layer and the copper layer, thereby achieving metallurgical bonding.
[0054] During the composite process, due to the relatively large deformation, the thickness of the composite material fluctuates greatly, and cold rolling with a small deformation is required to correct the material thickness. In some embodiments, in step S5, the rolling deformation does not exceed 20%, and the rolling speed is 0.5 to 20 m / min, so that the material has a uniform thickness.
[0055] In order to make the above-mentioned multi-layer material strip into the final product, in some embodiments, in step S6, direct blanking includes: directly punching the rolled material strip into the required layered composite contact to form an electrical contact. Striping and then rolling includes: dividing the rolled material strip into a plurality of narrow material strips, and then rolling to obtain a layered composite contact strip with a pattern on the welding surface. The pattern used as the welding surface is formed on one side of the iron-based material. On the one hand, the patterned surface plays an identification role; on the other hand, because the multi-layer composite material is generally welded on the bimetallic sheet, if the iron-based material surface has no pattern, it is difficult to weld or the welding firmness is poor. The use of the patterned surface can improve the welding firmness. For example, the pattern is a diamond pattern or a stripe pattern, etc. Different patterns can be selected for welding according to different bimetallic materials.
[0056] Another embodiment of the present invention provides a layered composite electrical contact material, which is prepared using the above-mentioned method for preparing the layered composite electrical contact material. The layered composite electrical contact material sequentially includes a silver-based working layer, a pure silver layer, a solder layer, a copper-based intermediate layer and an iron-based welding layer. Each material layer is a plate or a strip. The solder layer forms a metallurgical bond with the pure silver layer and the copper-based intermediate layer, respectively, and a fused metallurgical layer is formed between the pure silver layer and the copper-based intermediate layer.
[0057] The most important core part of the thermostat is the thermal protector, which is mainly responsible for controlling the on and off of the circuit when the temperature reaches a certain set value. The structure of the thermal protector mainly includes: contacts, bimetallic strips and other auxiliary systems. Since the bimetallic strip is mainly made of nickel-iron alloy and the welding method is mainly convex welding, the materials that can be welded with the bimetallic strip can only be nickel-based or iron-based materials. Therefore, the contact requirements must not only meet the welding requirements, but also have low resistance and breaking capacity. Therefore, three-layer structure contacts are often selected. The existing materials are generally in the form of three-layer composites, and the layered composite materials formed have only three layers. The three layers of materials are directly and simply composited; after heat treatment, the traditional three-layer composite material forms an extremely thin (tens to hundreds of nanometers) transition layer between each layer. This transition layer is used in a high temperature environment, the strength is extremely poor, and the contacts are easy to delaminate. The embodiment of the present invention forms a four-layer structure by first compounding solder, Cu and iron-based materials separately and then compounding them. The above embodiment of the present invention introduces a solder layer. After heat treatment, the solder layer will melt and form a metallurgical layer with the pure silver layer and the copper-based material to achieve the function of a "welding layer", so that the material has welding properties. A layer similar to a welding layer is formed between the silver layer and the copper layer. The performance of a complex welding process is achieved by a simple composite process. Moreover, this metallurgical layer is relatively thick (tens of microns), which can effectively improve its heat resistance. When used in a cold or hot environment, no stratification will occur. At the same time, the composite deformation does not need to be too large to avoid material cracking, effectively improving the yield rate. The electrical contact material can be used in the field of thermostats.
[0058] The thickness of each layer of material mainly affects the number of times the temperature controller operates, while the performance of the material itself affects its breaking capacity. Multilayer composite contact materials, especially the welding layer, are iron-based or nickel-based materials, which are used in the field of temperature sensors and need to be welded on bimetallic strips for use in combination. This means that the proportion of iron-based or nickel-based welding layers cannot be too thin, otherwise it will easily peel off after welding; and the proportion of silver-based materials generally does not exceed 30%, mainly because the temperature controller requires the product's breaking capacity, not the number of operations (the number of operations is generally not more than 5,000 times). In some embodiments, the thickness of the silver-based working layer accounts for 5% to 30% of the total thickness of the layered composite electrical contact material, and the sum of the thickness of the pure silver layer, solder layer, copper-based intermediate layer, and iron-based welding layer accounts for 30% to 90% of the total thickness of the layered composite electrical contact material. As a result, the application requirements in the field of temperature sensors can be met.
[0059] In the above embodiment of the present invention, a solder layer is pre-compounded on the silver-based material and the pure silver layer, and then subjected to high-temperature heat treatment, so that the solder layer is melted and fused with the pure silver layer; then, after cold compounding with the copper-based material and the iron-based material, high-temperature heat treatment is performed again, and the intermediate solder fusion layer is melted, and further fused with the copper-based material to form a metallurgical layer, which greatly improves the bonding strength between the silver-based material and the copper-based material, and the interface has good temperature resistance, avoiding the interface stratification problem under hot working conditions, thereby effectively improving the quality stability of the electrical contact and the product yield rate. The above embodiment of the present invention has a simple method, is easy to mass produce, and greatly reduces the production cost of the product.
[0060] The above-mentioned embodiments of the present invention meet the requirements for composite interface bonding under the condition of cold composite with a relatively small deformation, thereby solving the problem that the composite interface strength can only be achieved under a large composite deformation in conventional cold composite, and further solving the problem of edge cracking of silver-based oxide materials accompanying conventional large deformation composite, as well as the problem of delamination of layered contacts during service due to poor interface temperature resistance.
[0061] The scheme of the present application will be explained below in conjunction with specific embodiments and comparative examples. It will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained through commercial channels.
[0062] Example 1
[0063] This embodiment provides a method for preparing a AgSnO2(12) / Cu / Fe (12 represents that the mass proportion of SnO2 in the AgSnO2 material is 12%, and accordingly, the weight proportion of Ag is 88%) layered composite material, comprising the following steps:
[0064] Step 1: Continuously heat-reinforce the AgSnO2(12) strip with a width of 40 mm and a thickness of 6.0 mm, the pure silver strip with a width of 40 mm and a thickness of 1.0 mm, and the solder (solder) AgCuP with a width of 40 mm and a thickness of 0.4 mm at a temperature of 900 ° C, a nitrogen protective atmosphere, and a flow rate of 5 m -3 / h, the composite speed is 10m / min, and the composite deformation is 60%; after the composite is completed, the material strip is heat treated at 700℃ and the speed is 5m / min, so that the solder melts and fuses with the silver layer to obtain a three-layer AgSnO2(12) composite material with a thickness of 2.96mm.
[0065] The second step: cold-compound two layers of copper-based material with a width of 40 mm and a thickness of 10.0 mm and iron-based material with a thickness of 20.0 mm, and deform the composite by 90%. Then, heat-treat the material at a temperature of 900°C in a nitrogen-hydrogen mixed gas atmosphere to obtain a two-layer copper-iron-based composite material with a width of 40 mm and a thickness of 3.0 mm.
[0066] Step 3: The three-layer AgSnO2(12) composite material obtained in the first step and the two-layer copper-iron-based composite material with a thickness of 3.0 mm obtained in the second step are respectively washed with deionized water, dried at 100°C, and brushed online, and then cold-compounded with a composite deformation of 60% and a continuous composite speed of 0.1 m / min to obtain a silver-based layered composite electrical contact material with a thickness of 2.38 mm.
[0067] Step 4: Heat treat the material obtained in step 3 at a temperature of 750°C, a speed of 5m / min, argon protection, and a gas flow rate of 5m -3 / h, a layered AgSnO2 composite tape with high interface bonding strength was obtained.
[0068] Step 5: Roll the composite strip obtained in the fourth step with a deformation of 20% and a rolling speed of 0.5 m / min to obtain the required thickness of 1.91 mm.
[0069] Step 6: Punch and blank the 1.91 mm composite material strip obtained in the fourth step to obtain a AgSnO2(12) layered composite contact with a diameter of 10 mm and a thickness of 1.91 mm.
[0070] Figure 1 This is a microstructural metallographic image of the interface fusion distribution of Cu and Ag in the AgSnO2(12) / Cu / Fe layered composite material prepared in Example 1. The bottom layer is the AgSnO2(12) organizational structure, the top layer is the Cu layer, the "metallurgical fusion layer" of the solder is between the Cu layer and the Ag layer, and there are no defects such as holes and inclusions on the interface.
[0071] Figure 2 The AgSnO2(12) / Cu / Fe layered composite material was prepared in Example 1. Detailed image of the fusion zone at the interface between Cu and Ag. The microstructure of the middle "fusion zone" is an alloy structure with uniform structure and no defects such as pores and microstructure segregation.
[0072] This embodiment obtains AgSnO2(12) / Cu / Fe layered composite materials with good performance, wherein in the layered structure, a fused metallurgical layer is formed between the Ag layer and the Cu layer, the working surface AgSnO2(12) has no cracks, and the interface bonding strength is 90N / m 2 The product has good temperature resistance, the electrical life is increased by 25%, and the yield rate is increased by 20%.
[0073] Example 2
[0074] This embodiment provides a method for preparing a AgCdO(17) / Cu / Fe layered composite material, comprising the following steps:
[0075] Step 1: Continuously heat-reinforce the AgSnO2(17) strip with a width of 30 mm and a thickness of 5.0 mm, the pure silver strip with a width of 30 mm and a thickness of 0.8 mm, and the solder CuP with a width of 30 mm and a thickness of 0.2 mm at a temperature of 800 ° C, with an argon protective atmosphere and a flow rate of 2.8 m -3 / h, speed of 3m / min, composite deformation of 80%; after completion of the composite, the strip was heat treated at 800°C, speed of 10m / min, so that the solder melted and fused with the silver layer to obtain a three-layer AgCdO(17) composite material with a thickness of 1.2mm.
[0076] The second step: thermally composite a copper-based material with a width of 30 mm and a thickness of 3.0 mm and an iron-based material with a thickness of 6.0 mm in two layers, deform the composite by 50%, and then perform heat treatment at a temperature of 600°C in a heat treatment atmosphere of a hydrogen mixed gas to obtain a copper-iron-based composite material with a width of 30 mm and a thickness of 4.5 mm in two layers.
[0077] Step 3: The three-layer AgCdO(17) composite material obtained in the first step and the two-layer copper-iron-based composite material with a thickness of 4.5 mm obtained in the second step are respectively washed with deionized water, dried at 40°C, and brushed online, and then cold-compounded with a composite deformation of 50% and a continuous composite speed of 0.5 m / min to obtain a 2.85 mm thick AgCdO(17) / Cu / Fe layered composite electrical contact material.
[0078] Step 4: Heat treat the material obtained in step 3 at a temperature of 500°C, a speed of 4.5m / min, and a gas flow rate of 2.7m -3 / h, and a AgCdO(17) / Cu / Fe layered composite tape with high interface bonding strength was obtained.
[0079] Step 5: Roll the composite strip obtained in the fourth step with a deformation of 10% and a rolling speed of 20 m / min to obtain the required thickness of 2.57 m.
[0080] Step 6: Punch and blank the 2.57 mm composite material strip obtained in the fourth step to obtain a AgCdO(17) / Cu / Fe layered composite contact with a diameter of 6.5 mm and a thickness of 2.5 mm.
[0081] This embodiment finally obtains AgCdO(17) / Cu / Fe layered composite material with good performance, wherein in the layered structure, a fusion metallurgical layer is formed between the Ag layer and the Cu layer, the working surface AgCdO(17) has no cracks, and the interface bonding force is 85N / m2 The product has good temperature resistance, the electrical life is increased by 30%, and the yield rate is increased by 35%.
[0082] Example 3
[0083] This embodiment provides a method for preparing a AgNi(15) / Cu / Fe layered composite material, comprising the following steps:
[0084] Step 1: The AgNi (15) strip with a width of 50 mm and a thickness of 4.0 mm and the solder CuP with a width of 50 mm and a thickness of 0.05 mm are continuously thermally compounded at a temperature of 580 ° C, with an argon protective atmosphere and a flow rate of 0.2 m -3 / h, speed of 0.1m / min, composite deformation of 80%; after completion of the composite, the strip was heat treated at 550°C at a speed of 10m / min to melt the solder and fuse it with the silver layer to obtain a three-layer AgNi(15) composite material with a thickness of 0.81mm.
[0085] Step 2: Cold composite a copper-based material with a width of 50 mm and a thickness of 2.0 mm and an iron-based material with a thickness of 3.0 mm in two layers, with a composite deformation of 70%, and then heat treated at a temperature of 800°C in a nitrogen atmosphere to obtain a copper-iron-based composite material with a width of 50 mm and a thickness of 1.5 mm in two layers.
[0086] The third step: the two-layer AgNi(15) composite material obtained in the first step and the two-layer copper-iron-based composite material with a thickness of 1.5 mm obtained in the second step are respectively washed with deionized water, dried at 80°C, and brushed online, and then cold-compounded with a composite deformation of 20% and a continuous composite speed of 10 m / min to obtain a AgNi15 / Cu / Fe layered composite electrical contact material with a thickness of 1.848 mm.
[0087] Step 4: Heat treat the material obtained in step 3 at a temperature of 600°C, a speed of 0.2m / min, and a gas flow rate of 0.2m -3 / h. The AgNi(15) / Cu / Fe layered composite tape with high interface bonding strength was obtained.
[0088] Step 5: Roll the composite strip obtained in the fourth step with a deformation of 5% and a rolling speed of 10 m / min to obtain the required thickness of 1.75 m.
[0089] Step 6: Punch and blank the 1.75 mm composite strip obtained in the fourth step to obtain an AgNi(15) / Cu / Fe layered composite contact with a diameter of 8.0 mm and a thickness of 1.7 mm.
[0090] This embodiment finally obtains AgNi(15) / Cu / Fe layered composite material with good performance, wherein a fused metallurgical layer is formed between the Ag layer and the Cu layer in the layered structure, and the interface bonding force is 85N / m 2 The product has good temperature resistance, the electrical life is increased by 35%, and the yield rate is increased by 15%.
[0091] Example 4
[0092] This embodiment provides a method for preparing a AgZnO(15) / Cu / Fe layered composite material, comprising the following steps:
[0093] Step 1: Continuously heat-reinforce the AgZnO (15) strip with a width of 45 mm and a thickness of 3.5 mm; the pure Ag strip with a width of 45 mm and a thickness of 1.4 mm; and the solder AgCuP with a width of 45 mm and a thickness of 0.1 mm at a temperature of 780 ° C, a nitrogen protective atmosphere, and a flow rate of 0.3 m -3 / h, speed of 0.1m / min, composite deformation of 68%; after completion of the composite, the strip was heat treated at 750℃, speed of 3.5m / min, so that the solder melted and fused with the silver layer to obtain a three-layer AgZnO(15) composite material with a thickness of 1.6mm.
[0094] Step 2: Cold composite two layers of copper-based material with a width of 45 mm and a thickness of 2.0 mm and iron-based material with a thickness of 4.0 mm, with a composite deformation of 70%, and then heat treated at a temperature of 850°C in a hydrogen atmosphere to obtain a two-layer copper-iron-based composite material with a width of 45 mm and a thickness of 1.8 mm.
[0095] The third step: the three-layer AgZnO (15) composite material obtained in the first step and the two-layer copper-iron based composite material with a thickness of 1.6 mm obtained in the second step are respectively washed with deionized water, dried at 85°C, and brushed online, and then cold-compounded with a composite deformation of 60% and a continuous composite speed of 5 m / min to obtain a 1.36 mm thick AgZnO15 / Cu / Fe layered composite electrical contact material.
[0096] Step 4: Heat treat the material obtained in step 3 at a temperature of 700°C, a speed of 2.2 m / min, and a gas flow rate of 1.8 m -3 / h. The AgZnO(15) / Cu / Fe layered composite tape with high interface bonding strength was obtained.
[0097] Step 5: Roll the composite strip obtained in the fourth step with a deformation of 2% and a rolling speed of 10 m / min to obtain the required thickness of 1.33 m.
[0098] Step 6: Punch and blank the 1.33 mm composite strip obtained in the fourth step to obtain a AgZnO(15) / Cu / Fe layered composite contact with a diameter of 5.0 mm and a thickness of 1.3 mm.
[0099] Taking AgZnO(15) / Cu / Fe layered composite material as an example, due to the poor plasticity of AgZnO(15) material, when the traditional composite deformation is more than 70% or more, AgZnO(15) will crack under large deformation, making its overall yield rate less than 50%. In the above embodiment of the present invention, AgZnO(15) and solder are first composited, and then Cu and Fe are composited; finally, the total composite is performed; due to the use of solder, the composite deformation does not need to be like the traditional multi-layer composite, and the deformation must reach more than 70% to ensure the bonding strength. The above embodiment of the present invention uses a solder auxiliary layer, and the last composite plays a fixing role. The improvement of the composite interface bonding strength is determined by the melting of the solder in the subsequent heat treatment process to form a metallurgical layer. Therefore, the material can be well protected from cracking due to large deformation, and the yield rate can be significantly improved while improving the interface bonding strength.
[0100] This embodiment finally obtains AgZnO(15) / Cu / Fe layered composite material with good performance, wherein a fused metallurgical layer is formed between the Ag layer and the Cu layer in the layered structure, and the interface bonding force is 90N / m 2 The product has good temperature resistance, the electrical life is increased by 18%, and the yield rate is increased by 26%.
[0101] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essence of the present invention. The above preferred features can be used in any combination without conflicting with each other.
Claims
1. A method for preparing a layered composite electrical contact material, characterized in that: include: The silver-based working layer, the pure silver layer and the solder layer are continuously thermally compounded, and then continuously heat treated to fuse the solder layer and the pure silver layer to obtain a three-layer composite material; Compounding the copper-based material and the iron-based material in two layers and heat treating them to obtain a two-layer copper-iron-based composite material; Cold-compounding the three-layer composite material and the two-layer copper-iron-based composite material to obtain a silver-based layered composite electrical contact material; The silver-based layered composite electrical contact material is subjected to high-temperature heat treatment so that the solder layer and the copper-based material are fused to obtain a material strip; Rolling the strip to a desired thickness; The rolled material strip is directly blanked or cut into strips and then rolled to obtain a layered composite electrical contact material of required specifications.
2. The method for preparing a layered composite electrical contact material according to claim 1, characterized in that: The silver-based working layer, the pure silver layer and the solder layer are continuously thermally composited and then continuously heat treated, wherein: The thickness of the solder layer is 0.05 to 0.4 mm; The thermal compound atmosphere is argon or nitrogen atmosphere, and the flow rate is 0.2~5m -3 / h; the thermal composite temperature is 580~900℃; the material pulling speed is 0.1~10m / min, and the composite deformation is 60%~90%; The continuous heat treatment temperature is 550°C to 800°C, and the speed is 0.5 to 10 m / min.
3. The method for preparing a layered composite electrical contact material according to claim 1, characterized in that: The copper-based material and the iron-based material are subjected to two-layer composite and heat treatment, wherein: cold composite or hot composite is adopted, the composite deformation amount is 50% to 90%, the heat treatment temperature is 600° C. to 900° C., and the heat treatment atmosphere is any one of hydrogen, nitrogen and nitrogen-hydrogen mixed gas.
4. The method for preparing a layered composite electrical contact material according to claim 1, characterized in that: The three-layer composite material and the two-layer copper-iron-based composite material are cold-compounded, wherein: the cold-compounding deformation is 20% to 60%, the thickness of the solder fusion layer after compounding is within 0.1mm, and the cold-compounding speed is 0.1 to 10m / min.
5. The method for preparing a layered composite electrical contact material according to claim 1, characterized in that: The silver-based composite electrical contact material is subjected to high-temperature heat treatment, wherein: the protective atmosphere is any one of argon, nitrogen, and a mixture of argon and nitrogen, and the gas flow rate is 0.2 to 5 m -3 / h; the temperature is 500-750°C, and the material pulling speed is 0.2-5m / min.
6. The method for preparing a layered composite electrical contact material according to claim 1, characterized in that: The material strip is rolled to a desired thickness, wherein the rolling deformation does not exceed 20% and the rolling speed is 0.5-20 m / min.
7. The method for preparing a layered composite electrical contact material according to claim 1, characterized in that: The rolled strip is directly blanked or stripped and then rolled, wherein: The direct blanking includes: directly punching the rolled material strip into the required layered composite contacts; The stripping followed by rolling comprises: dividing the rolled material strip into a plurality of narrow material strips, and then rolling them to obtain a layered composite joint strip with patterns on the welding surface.
8. A layered composite electric contact material, prepared by the method for preparing a layered composite electric contact material according to any one of claims 1 to 7, characterized in that: The layered composite electrical contact material comprises a silver-based working layer, a pure silver layer, a solder layer, a copper-based intermediate layer and an iron-based welding layer in sequence, each material layer is a plate or a strip, and the solder layer forms a metallurgical bond with the pure silver layer and the copper-based intermediate layer respectively.
9. The layered composite electrical contact material according to claim 8, characterized in that: The thickness of the silver-based working layer accounts for 5% to 30% of the total thickness of the layered composite electrical contact material, and the sum of the thickness of the pure silver layer, solder layer, copper-based intermediate layer and iron-based welding layer accounts for 30% to 90% of the total thickness of the layered composite electrical contact material.
10. The layered composite electrical contact material according to claim 8, characterized in that: The material of the silver-based working layer is any one of AgSnO2, AgNi, AgCdO, AgCuO, AgZnO and AgFe; The material of the solder layer is silver alloy solder or copper alloy solder; The material of the copper-based intermediate layer is metallic copper or a copper-based alloy; The material of the iron-based welding layer is metallic iron or iron-based alloy.
Citation Information
Patent Citations
Ag base three-layer metal compound electrical contact material
CN101034632A
Silver-based multi-layer composite electrical contact material and preparation method thereof
CN107591257A